2006
DOI: 10.1117/1.2337546
|View full text |Cite
|
Sign up to set email alerts
|

In vivo absorption, scattering, and physiologic properties of 58 malignant breast tumors determined by broadband diffuse optical spectroscopy

Abstract: Diffuse optical imaging (DOI) may be a beneficial diagnostic method for women with mammographically dense breast tissue. In order to evaluate the utility of DOI, we are developing broadband diffuse optical spectroscopy (DOS) to characterize the functional origins of optical signals in breast cancer patients. Broadband DOS combines multifrequency intensity-modulated and continuous-wave near-infrared light to quantify tissue absorption and scattering spectra from 650 to 1000 nm. Values of intrinsic physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
435
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(458 citation statements)
references
References 78 publications
19
435
1
3
Order By: Relevance
“…Intra-and interobserver agreement were good to excellent, indicating a reproducible method. Our results are in agreement with previously published studies using different techniques [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Detection rates ranging from 0.04 to 1.00 were reported, irrespective of lesion classification (benign/malignant).…”
Section: Discussionsupporting
confidence: 83%
“…Intra-and interobserver agreement were good to excellent, indicating a reproducible method. Our results are in agreement with previously published studies using different techniques [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Detection rates ranging from 0.04 to 1.00 were reported, irrespective of lesion classification (benign/malignant).…”
Section: Discussionsupporting
confidence: 83%
“…Several investigators report an increase in diagnostic accuracy. Using diffuse optical spectroscopy (DOS) Cerussi et al [110] found intrinsic physiologic features of malignancy to significantly differ from normal glandular breast tissue: all malignant lesions had lower lipid content than normal breast tissue but higher water, desoxy-, and oxyhemoglobin content. Zhu et al [32] and Fang et al [111] also report significant differences in hemoglobin concentration between malignant and benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The ranges for ÎŒ a and ÎŒ s were selected based on the typical optical properties of breast tissue. 4 In the first experiment, we used a reference solution of 3.2% by volume (32 ml/l) of Intralipid R 20% with no added ink or dye. This provides a medium where the absorption is predominantly due to water, which results in higher absorption at higher wavelengths (expected 0.042, 0.068, cm −1 @ 780, 808, 850, 904 nm).…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] These handheld probes image in reflectance mode with a 0.5-3.5 cm sourcedetector separation in order to probe beneath the tissue surface. They use a range of near-infrared wavelengths to determine the concentration of chromophores relevant to detecting tumors including oxy-and deoxy-hemoglobin, lipid, water, and scattering.…”
Section: Introductionmentioning
confidence: 99%